Educators’ reasoning(s) and their effects on successful attainment of curriculum goals - Makumane, M.A.; Khoza, S.B. (South African Journal of Higher Education, 2020)
It has been suggested that the curriculum development process should focus on three factors: people, programmes and process in order to achieve the idealised goals. In other words, for a curriculum to be successfully enacted, it should encompass societal needs (social reasoning), facts as representative of a specific discipline (professional reasoning) and the unique strategies adopted by the educator to attain desired goals (personal reasoning). These three factors are driven and influenced by educators’ reasoning (social, professional and personal), which drive and have an impact on their practice. The purpose of this article is to explore three propositions of educators’ reasoning. Such reasoning is divided into personal, social, and professional reasonings, and their effects on successful attainment of curriculum goals. Using an interpretive qualitative case study, 20 participants were selected using purposive sampling: with two selected using convenience sampling for the reported study. Data were generated using reflective activities and one-on-one semi-structured interviews. The findings demonstrate that being grounded in either social or professional reasoning, while disregarding the other, may hamper the attainment of goals. Thus, this article recommends integration and alignment of the three propositions of reasoning (personal, social, and professional) in order to successfully attain curriculum goals.